Le mythe du microcèbe primitif - Fabien Génin; Judith C Masters (Revue de Primatologie)
Mouse lemurs (genus Microcebus, family Cheirogaleidae) are small, nocturnal lemurs endemic to Madagascar, often viewed as the most archaic primates. In this contribution, we criticise this almost mythical view, which is neither supported by the fossil record nor by the most recent phylogenies. We propose the alternative hypothesis of a reduction of body size, or dwarfism, a phenomenon known to occur frequently on islands, and in isolated regions subject to El Niño-related unpredictable droughts. We confirm Gould’s model of progenesis, which explains dwarfism by hypervariability leading to acceleration of life history. Cheirogaleids appear as paedomorphic dwarfs compared to their sister-taxon, the Lepilemuridae (Lepilemur). They probably experienced at least 3 independent events of dwarfing which lead to parallel changes in the proportions of the head and limbs (allometry). The first one (dwarfing) has led to a decrease in the size of body and limbs, without any significant change in cranial form (with the exception of teeth) in the largest forms Phaner, Mirza, and the largest forms of the genus Cheirogaleus). The second (hyper-dwarfing) has led to parallel changes in cranial form in the smallest taxa (Allocebus, Microcebus and the smaller forms of the genus Cheirogaleus), associated with typical paedomorphic traits (large eyes and small, pointed snout). This new interpretation explains many unique characteristics of this group of lemurs, in particular their rapid life histories.